Studi Perbandingan Prosedur Penanganan Barang Perishable untuk Cold Storage di Pelabuhan dan Bandara Internasional di Jakarta - Lis Lesmini; Wynd Rizaldy (Institut Transportasi dan Logistik Trisakti, 2021)
This study aims to analyze the different handling procedures of Perishable goods in the cold storage area at the seaport and airport in Jakarta, as well as to increase the efficiency, benefits of more effective and efficient warehousing in the flow of the handling process. The location of this research is at Tanjung Priok Port and Soekarno Hatta Airport. The research's focus on surveying the location where observation is carried out in closed and open warehouses also conducts layout analysis and observes, studies the process of receiving and storing goods in the warehouse. This research is descriptive qualitative to describe in-depth about the different procedures for handling perishable goods at seaports and airports in Jakarta. The data are primary and secondary. Primary data from interviews and surveys, secondary data from the company, and various supporting literature. The research informants were Cold Storage business players at ports and airports as well as from the Indonesian Cold Chain Association. The data analysis technique used the approach developed by Miles and Huberman. The results showed the differences in both procedures, capacities, and reference standards, although the type of goods handled was the same as perishable goods.